Genauigkeitsuntersuchung von binokularen Normalenvektoren für die Umfeldwahrnehmung - Harms, Hannes (Schriftenreihe / Institut für Mess- und Regelungstechnik, Karlsruher Institut für Technologie, 2017)
The presented work introduces an accuracy analysis of normal vectors from binocular camera systems, which allows to model the surface orientation uncertainties by considering few parameters. The results of the accuracy analysis are used to design two methods for environment perception: a free space estimation for vehicles as well as the staircase detection for visually impaired persons.